Comparison of Preoperative Ultrasound Report with Intraoperative Findings of Laparoscopic Cholecystectomy in Gallstone Disease in Al-Diwaniyah Teaching Hospital - Adel Shakir Al-Timimi1, Anwar Majeed Hussein1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Gallstones constitute a significant health problem in developed societies, affecting 10% to 15% of the adult population, meaning 20 to 25 million Americans have (or will have) gallstones. The resultant direct and indirect cost of gallbladder disease represents a consumption of 6.2 billion annually in the U.S., constituting a major health burden that has increased more than 20% over the last 3 decades. The best diagnostic tool is ultrasound; however, several authosr have raised the issue of inconsistency between preoperative ultrasound evaluation and laparoscopic operative findings.Aim of the study: To compare preoperative ultrasound findings with operative findings in patients undergoing laparoscopic cholecystectomy in order to evaluate the accuracy of ultrasound in detecting gallbladder pathology.Patients and Method: In this hospital based study, in order to evaluate the concordance and discrepancy between preoperative ultrasound findings and operative findings in patients subjected to laparoscopic cholecystectomy. At the end of study we were able to include 100 cases. The study started on January the 2nd 2019 and ended at June the 15th 2019. The study was carried out at laparoscopic unit in Al-Diwaniyah teaching hospital. Ultrasound findings were retrieved from available reports that are already kept with the case file sheet of each patient. Operative findings were obtained the surgery team and by the use of a special device which provide information about size of stone and gallbladder wall thickness.Results: Regarding number of stones and for purpose of unification both ultrasound sound findings and operative findings were contrasted as single stone versus multiple stones, as shown in table 2. Indeed, there was almost complete agreement between ultrasound and operative findings since 22 patients were diagnosed as having single stone by both methods and 76 were diagnosed as having multiple stones by both methods. According to MeNemar test, there was no significant difference in distribution of patients into having single versus multiple stones (P = 1.000), a finding that was further supported by Kappa agreement statistic of 0.944 (P < 0.001), table 4.3.